Meconium stained liquor and perinatal outcome - Biradar, Aruna; Kori, Shreedevi; Patil, Neelamma; Mudanur, S. R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study is to know the association between the meconium stained amniotic fluid and its association with the perinatal outcome. Methods: All the patients coming to present hospital for delivery with meconium stained liquor during the study period were included in the study. Results: 163 cases with meconium stained liquor (MSAF) were included in the study, 124(76.1%) and 39(23.9%) had thin and thick MSAF respectively. Among these cases, thick MSAF was more associated with high fetal heart rate (FHR) variability (p value- 0.030), associated with increased rate of operative interference (64.1%; p value- 0.001), abnormal Apgar score (p value-0.003 at 1min and 0.001 at 5min) and increased neonatal intensive care unit (NICU) admission (33.3%; p value - <0.001). Conclusions: Present study showed that thick meconium is associated with more complications like increased operative interference, birth asphyxia, meconium aspiration syndrome, low Apgar score, prolonged NICU stay and overall increased perinatal mortality compared to thin meconium stained liquor. As the gestational age increased the incidence of meconium increased and a greater number of thick meconium had abnormal CTG.